A new prototype system for automated suppression of disc brake squeal. (April 2021) - Budinsky, Tomas; Brooks, Peter; Barton, David
This paper presents a new prototype system capable of automated disc brake squeal suppression using a method of varying the leading and trailing piston pressures in a multi-piston opposed brake caliper. The new system consists of a novel modular four-piston brake caliper, a two-channel brake actuation system and an advanced control system that is capable of varying the leading/trailing pressure ratio (LTPR) when squeal is detected. The amended LTPR results in movement of the centre of pressure (CoP) position at the pad/disc interface, which leads to new dynamic parameters of the brake system and thereby to different squeal propensity. Moreover, the control system maintains the overall brake torque at a constant value, so the variation of the LTPR on the brake performance is minimised. Experiments using the current disc brake setup showed that by varying the LTPR, thereby changing the CoP position, the squeal occurrence can be successfully controlled. Large leading or trailing offsets typically lead to a quieter brake. Tests demonstrating operation of the proposed squeal control system in an automatic mode reduced the squeal occurrence significantly for a given duty cycle.